1983
DOI: 10.1007/bf00510050
|View full text |Cite
|
Sign up to set email alerts
|

Immunocompetent cells in psoriasis

Abstract: Immunocompetent cells in exacerbating untreated psoriasis vulgaris skin lesions were immunophenotypically studied by the application of a selection of monoclonal antibodies in a two-stage immunoperoxidase technique. Epidermal changes include: focal accumulation of immunoglobulins in the stratum corneum, as demonstrated by a mixture of monoclonal anti-kappa and anti-lambda antibodies; focal accumulation of OKM-1 positive but Mo-2 negative cells high in the epidermis, reflecting granulocytes in Munro's abscesses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
1
6

Year Published

1985
1985
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(89 citation statements)
references
References 23 publications
4
78
1
6
Order By: Relevance
“…+ and γδ-T cells [2][3][4]. Psoriasis affects approximately 2% of people of both sexes [5], with diminished quality of life [6] and significant co-morbidities [7].…”
Section: Introductionmentioning
confidence: 99%
“…+ and γδ-T cells [2][3][4]. Psoriasis affects approximately 2% of people of both sexes [5], with diminished quality of life [6] and significant co-morbidities [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperproliferation of keratinocytes in the psoriatic plaques is triggered by infiltrating T-lymphocytes at the dermal-epidermal junction (13). Keratinocytes in the uninvolved skin of psoriatic patients have an inherent sensitivity to proliferative signals, and this elevated sensitivity plays a crucial role in the development of psoriatic lesions (14,15).…”
mentioning
confidence: 99%
“…NB-UVB phototherapy has a higher ratio of therapeutic to erythemogenic activity, resulting in increased efficacy, reduced incidence of burning and longer remission. Results from two therapeutic action spectroscopy studies indicated that wavelengths of the range 295-320 nm are effective in clearing psoriasis, whereas shorter wavelengths are more erythemogenic, and wavelengths longer than 320 are less therapeutic [37,38]. Subsequent clinical studies have tended to report significantly greater improvement of psoriasis with NB-UVB including reduced incidence of burning episodes, increased efficacy and longer remission when compared with broad band sources [39].…”
Section: Conventional Phototherapymentioning
confidence: 99%
“…The Soret band (approximately 405-420 nm) is the most important excitation peak for protoporphyrin IX and is included in the spectral output of the US Food and Drug Administration (FDA)-approved Blu-U device, which is used with ALA. Another peak in the excitation spectrum for porphyrins includes red light at approximately 635 nm, which is targeted by different devices, including those approved to be used with MAL [34,[36][37][38].…”
Section: Photodynamic Therapymentioning
confidence: 99%